Temperature-induced flexibility of graphene sheet facilitates RNA duplex unzipping: A molecular dynamics study - Maksym V. Karachevtsev; Victor A. Karachevtsev (AIP Advances)
Many genetic processes are based on unzipping the DNA/RNA double helix. Therefore, the development of methods for rapid duplex unzipping is highly desirable for biomedical applications. In this work, we propose a novel approach to unzipping a DNA/RNA duplex by exploiting the ability to induce flexibility of a graphene sheet that can facilitate the unzipping of an adsorbed duplex. As an example of tunable and inducible flexibility of a graphene sheet, we used temperature-dependent flexibility of graphene sheet in our simulation. Molecular dynamics simulations demonstrated that duplex (rA)15:(rU)15 adsorbed on the flexible graphene sheet in a water environment unzipped at room temperature much faster than on graphene with fixed carbon atoms. Duplex unzipping begins with the terminated base pairs located in the tail of the duplex adsorbed on graphene. The distance between base pairs, number of H-bonds in the duplex, and interaction energy between (rA)15 and (rU)15 strands was determined when they were arranged on the flexible graphene sheet in an aqueous environment at 273, 303, and 333 K and compared to data obtained from a frozen graphene sheet. Analysis of the duplex structure at different temperatures showed that the flexible surface at room and lower temperatures is very effective in short-duplex unzipping, while at higher temperatures (333 K), this advantage of the flexible graphene sheet is negated.